Characterization of beam quality of unstable laser beams with the multiple hyperbolas method - Lingqiang Meng; Qingqing Kong; Kunhao Ji; Zhigang Han; Hua Shen; Rihong Zhu (Results in Physics, 2019)
In this paper, the multiple hyperbolas method is proposed for characterizing the beam quality of unstable laser beams. Based on the traditional beam quality analyzer equipment, the proposed method captures multiple intensity images at every measurement positions. Afterward, three different hyperbolas are fitted according to the widths of laser intensities. With the fitted hyperbolas, three parameters, which include the average beam quality factor (Maver2) and variation factors (νpos, νneg), are determined. With the proposed method and determined parameters, the beam quality of unstable laser beams can be characterized more accurately and completely. The limitation of the traditional ISO standard-based method for characterizing unstable laser beams is also presented. In addition, the simulation and experimental results agree well with each other, indicating that the new method and determined parameters are appropriate for characterizing unstable laser beams. Keywords: Laser beam delivery and diagnostics, Laser characteristic, Laser beam quality, Unstable laser beams